Tourist satisfaction and loyalty: A structural equation model (SEM) analysis - Mohd Salleh, Norlida Hanim; Sarmidi, Tamat; Othman, Redzuan; Jaafar, Abdul Hamid; Abdul Talib, Basri (2011)
This study attempts to analyze the relationship between tourist satisfaction and loyalty to the tourist destination of Taman Laut Pulau Kapas, a tourism destination.As to observe that relationship, 193 tourists have been interviewed. The interviews were carried out to get tourists’ responses relating to their satisfaction to the various aspects of tourism products, services, vacation trips, etc. A sum of 46 satisfaction detail is adduced to the tourists. The tourist’s demographic information, probability of revisiting and promoting the tourism destination upon returning from holiday are also attempted to be obtained. Here, the revisiting and promoting are indication to tourist loyalty on their holiday destination. Information from interviews will be analyzed using the Structural Equation Model (SEM) with computer package of Analysis Moment of Structural (AMOS 5.0). Survey result of all the 46 satisfaction details are grouped into four (4) groups/major variables, namely satisfaction on the whole trip, product diversification, support facilities and security. There is positive relationship between tourist satisfaction and the above mentioned variables. However, satisfaction and tourist loyalty for the Taman Laut Pulau Kapas case are found to be negatively related. Study also finds that the latent variables in this model have high Cronbach Alpha values which are at 0.88 and 0.81 respectively, and these prove that variables in the latent variables are suitable. Survey results also find that the correspondence decision value model, namely the chi square Goodness-of-Fit is not significant [χ2 (N=300, df=8) = 12.107 p>0.05], NFI correspondenceʹs index value, RFI, IFI, TLI and CFI exceed 0.90, and the RMSEA value is slightly smaller than 0.06 (RMSEA=0.051). Thus, the results confirm the measurement model reliability in structural equation model is as suggested by researchers.